Flexible Use of High-Density Oligonucleotide Arrays for Single-Nucleotide Polymorphism Discovery and Validation - Dong, Shoulian; Wang, Eugene; Hsie, Linda; Cao, Yanxiang; Chen, Xiaogiong; Gingeras, Thomas R. (Genome Research, 2001)
A method for identifying and validating single nucleotide polymorphisms (SNPs) with high-density oligonucleotide arrays without the need for locus-specific polymerase chain reactions (PCR) is described in this report. Genomic DNAs were divided into subsets with complexity of ∼10 Mb by restriction enzyme digestion and gel-based fragment size resolution, ligated to a common adaptor, and amplified with one primer in a single PCR reaction. As a demonstration of this approach, a total of 124 SNPs were located in 190 kb of genomic sequences distributed across the entire human genome by hybridizing to high-density variant detection arrays (VDA). A set of independent validation experiments was conducted for these SNPs employing bead-based affinity selection followed by hybridization of the affinity-selected SNP-containing fragments to the same VDA that was used to identify the SNPs. A total of 98.7% (74/75) of these SNPs were confirmed using both DNA dideoxynucleotide sequencing and the VDA methodologies. With flexible sample preparation, high-density oligonucleotide arrays can be tailored for even larger scale genome-wide SNP discovery as well as validation.